Speech Function Used in A little Princess of Frances Hodgson Burnett Novel - Wilany, Eka; Megah, Suswanto Ismadi; Iriyana, Ria (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
The study was aimed to describe kinds of speech function that used by the main character in A Little Princess novel. It was found in some statements from Sara Crewe in this novel. The research design applied qualitative research in which used the theory from Janet Holmes to categorize the utterances derived from list of data found in A Little Princess novel into 8 kinds of speech function (expressive, directive, referential, metalinguistic, phatic, poetic, heuristic and commissive). All of the classified data was interpreted concern with description of situation. Each of them was analysed based on Holmesâ€™Â theory. The result of this research showed that there found fifty Creweâ€™s utterances contained only five speech functions terms: expressive, directive, referential, phatic and commissive. From the result of the data analysis, it showed that the most dominant kind of speech function that used by Sara Crewe is expressive function as much as twenty utterances.It is hoped that by understanding kinds of speech functions and the use of them can help us create good communication and relationship with others. People need to understand the meaning to get the point to give appropriate responds to the speakers. Moreover, for EFL students, it can be contributed as one of analysis in sociolinguitics learning so that they can apply them in their utterances or statements. Lastly, it is hoped that this study can enrich the research in linguistics field especially for the term of speech function